Situating video as context for teacher learning. (September 2021) - Danish, Joshua A.; Johnson, Heather; Nicholas, Celeste; Cross Francis, Dionne; Hmelo-Silver, Cindy E.; Park Rogers, Meredith; Askew, Rachel; Gerber, Alex; Enyedy, Noel
Abstract: In this paper we contrast two locally situated models of supporting teacher learning using video reflection: a one-on-one coaching model that was implemented to support teachers in a wide-spread rural school district where in-person meetings were challenging, and a video club model that was implemented in a large, centrally organized school district. In both contexts our goal was to help elementary teachers learn about how they can support students in using representations to learn about science in their classrooms. We take a sociocultural approach to examining how the locally situated professional development models helped mediate the teachers' engagement with the video. Findings show that in both models, collaborative review of video cases helped the teachers to see new patterns and opportunities. We highlight how each was supported by the different models and offer suggestions for how future work can benefit from these opportunities.